A common SNP in the CD40 region is associated with systemic lupus erythematosus and correlates with altered CD40 expression: implications for the pathogenesis - (:unkn) unknown (BMJ PUBLISHING GROUP, 2011)
Background In systemic lupus erythematosus (SLE) sustained CD40L expression by T cells and platelets activates a variety of cells via its receptor CD40 contributing to disease pathogenesis. Although CD40 has recently been identified in genome-wide association study as a novel rheumatoid arthritis susceptibility gene such an association has not been documented for SLE. Objective To investigate whether the rs4810485 CD40 single nucleotide polymorphism (SNP) is associated with increased risk for SLE and its impact on CD40 expression. Materials and methods The primary sample set consisted of 351 patients with SLE and 670 matched healthy controls of Greek origin. 158 patients with SLE and 155 controls from Turkey were used as a replication sample. Genotyping of rs4810485 was performed by restriction fragment length polymorphism and the Sequenom MassArray technology. The expression of CD40 mRNA and protein was assessed in unstimulated and lipopolysaccharide-stimulated peripheral blood mononuclear cells by quantitative real time PCR and flow cytometry, respectively. Results The minor allele T of CD40 rs4810485 SNP was significantly under-represented in Greek patients with SLE compared with healthy controls (OR=0.65, 95% CI 0.54 to 0.79). The association was replicated in the Turkish cohort (OR=0.57, 95% CI 0.41 to 0.80; meta-analysis of 509 patients with SLE and 825 healthy controls: OR=0.63, 95% CI 0.53 to 0.74, p = 2x10(-8)). In both cases and controls, the rs4810485 G/T and T/T genotypes were associated with significantly reduced CD40 mRNA and protein expression in peripheral blood CD14+ monocytes and CD19+ B cells compared with G/G genotype, both under basal conditions and following stimulation. Conclusions CD40 has been identified as a new susceptibility locus in Greek and Turkish patients with SLE. The rs4810485 minor allele T is under-represented in SLE and correlates with reduced CD40 expression in peripheral blood monocytes and B cells, with potential implications for the regulation of aberrant immune responses in the disease.
Keywords: GENOME-WIDE ASSOCIATION; RHEUMATOID-ARTHRITIS SUSCEPTIBILITY; GENETICALLY HOMOGENEOUS POPULATION; STAT4 GENE POLYMORPHISM; AUTOIMMUNE-DISEASES; ENDOTHELIAL-CELLS; ANTI-CD40 LIGAND; RISK; SLE; CD40-CD40L